Навчально-методичне забезпечення формування у студентів рухових умінь і навичок гри в регбі = Teaching and methodical materials for training motive abilities and skills of students for playing rugby - Sabirov, O. (Journal of Education, Health and Sport, 2015)
Sabirov O. Навчально-методичне забезпечення формування у студентів рухових умінь і навичок гри в регбі = Teaching and methodical materials for training motive abilities and skills of students for playing rugby. Journal of Education, Health and Sport. 2015;5(3):325-334. ISSN 2391-8306. DOI: 10.5281/zenodo.31295 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A325-334 https://pbn.nauka.gov.pl/works/631280 http://dx.doi.org/10.5281/zenodo.31295 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015. Навчально-методичнЕ забезпечення формування у студентів рухових умінь і навичок гри в регбі Teaching and methodical materials for training motive abilities and skills of students for playing rugby Sabirov O. Сабіров О. С. Національний технічний університет України «Київський політехнічний інститут» National Technical University of Ukraine "Kyiv Polytechnic Institute" Навчально-методичне забезпечення формування рухових умінь і навичок студентів вищих навчальних закладів у процесі занять регбі включає засоби, методи та форми навчання; методику засвоєння прийомів індивідуальної та колективної техніки; послідовність навчальних дій; профілактика та способи виправлення можливих помилок. Формування рухових умінь і навичок – це тривалий і структурований процес, який складається з відносно завершених етапів. На першому етапі відбувається початкове вивчення техніки рухової дії, якому відповідає стадія утворення вміння. Другий етап характеризується поглибленим, деталізованим вивченням, в результаті чого відбувається формування рухової навички. На третьому етапі забезпечується закріплення і вдосконалення рухової дії в різних умовах ігрової діяльності. Ключові слова: рухові вміння, рухові навички, регбі, студенти, позааудиторні заняття. Sabirov O. Teaching and methodical materials for training motive abilities and skills of students for playing rugby. Teaching and methodical materials for training motive abilities and skills of students of higher educational institutions to play rugby at the practical classes include various means, methods and forms of teaching; methods of mastering the ways of individual and team techniques; succession of the teaching steps; prevention and correction of the possible mistakes. A formation of the motive abilities and skills is a long lasting structured process that consists of relatively finished stages. In the first stage students study primary phases of the techniques of motive actions which correspond to the formation of a skill. The second stage is characterized by a deeper and more detailed learning that results into a formation of a motive skill. In the third stage the students are trained to apply and improve a motive skill in various conditions of a game activity. Key words and phrases: motive abilities, motive skills, rugby, students, extracurricular lessons.